2023
DOI: 10.1371/journal.pone.0280515
|View full text |Cite
|
Sign up to set email alerts
|

Faster progression to multiple sclerosis disability is linked to neuronal pathways associated with neurodegeneration: An ethnicity study

Abstract: Although the causes of multiple sclerosis are largely unknown, genetic and environmental components play an important role. Geographic distribution, varying with latitude, reflects both genetic and environmental influences. We conducted a retrospective exploratory observational study to characterize the disability progression of 2396 Jewish patients with relapsing-remitting multiple sclerosis, followed at the Sheba Multiple Sclerosis Center, Tel-Aviv, Israel; 188 patients who originated in Iraq and 2207 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Harari et al, in an epidemiogenetical study that spanned over 18 years and involved a cohort of 2396 Jewish PwMS (Iraqi-born Jewish patients or Israeli-born Jewish patients with both parents born in Iraq vs. those of Northern European origin, who were partially treated with DMTs), concluded that patients of Iraqi origin tended to progress faster to an EDSS of 3.0 compared to those of Northern European origin. This emphasizes ethnic disparities in RRMS progression, although approximately half of the subjects from both cohorts reached an EDSS of at least 3.0—findings and methodology consistent with our study [ 56 ]. This variability depends on the heterogeneity of PwMS, accessibility to medical services, as well as genetic, socio-economic, and environmental factors.…”
Section: Discussionsupporting
confidence: 91%
“…Harari et al, in an epidemiogenetical study that spanned over 18 years and involved a cohort of 2396 Jewish PwMS (Iraqi-born Jewish patients or Israeli-born Jewish patients with both parents born in Iraq vs. those of Northern European origin, who were partially treated with DMTs), concluded that patients of Iraqi origin tended to progress faster to an EDSS of 3.0 compared to those of Northern European origin. This emphasizes ethnic disparities in RRMS progression, although approximately half of the subjects from both cohorts reached an EDSS of at least 3.0—findings and methodology consistent with our study [ 56 ]. This variability depends on the heterogeneity of PwMS, accessibility to medical services, as well as genetic, socio-economic, and environmental factors.…”
Section: Discussionsupporting
confidence: 91%
“…However, these characteristics predominantly represent an ongoing neuroinflammation. Meanwhile, neurodegeneration has been considered the driving force of disability progression [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%